Protein kinase C is essential for viability of the rice blast fungus Magnaporthe oryzae. Issue 3 (18th August 2015) - Penn, Tina J.; Wood, Mark E.; Soanes, Darren M.; Csukai, Michael; Corran, Andrew John; Talbot, Nicholas J.
Summary Protein kinase C constitutes a family of serine–threonine kinases found in all eukaryotes and implicated in a wide range of cellular functions, including regulation of cell growth, cellular differentiation and immunity. Here, we present three independent lines of evidence which indicate that protein kinase C is essential for viability of Magnaporthe oryzae. First, all attempts to generate a target deletion of PKC1, the single copy protein kinase C‐encoding gene, proved unsuccessful. Secondly, conditional gene silencing of PKC1 by RNA interference led to severely reduced growth of the fungus, which was reversed by targeted deletion of the Dicer2‐encoding gene, MDL2. Finally, selective kinase inhibition of protein kinase C by targeted allelic replacement with an analogue‐sensitive PKC1AS allele led to specific loss of fungal viability in the presence of the PP1 inhibitor. Global transcriptional profiling following selective PKC inhibition identified significant changes in gene expression associated with cell wall re‐modelling, autophagy, signal transduction and secondary metabolism. When considered together, these results suggest protein kinase C is essential for growth and development of M. oryzae with extensive downstream targets in addition to the cell integrity pathway. Targeting protein kinase C signalling may therefore prove an effective means of controlling rice blast disease.